Why a Center for Biblical Studies? - Marga, Andrei (Sacra scripta, 2003)
The Centre for Biblical Studies is a centre for research, in which prevail the investigation, the proofs, and the argumentative dialogue. It is not a common Centre and it is clear that a number of changes – at least as far as the public perception on religion is concerned – will have to occur. I have three such changes in view: a)those saying that they keep away from religion will have to accept that the field of religion, and, more specifically, the field of the ancient book that is the Bible is the ground on which many aspects of the fate of humanity are decided, and that, consequently, the research of the Bible is not relevant for theologians alone; b)the theologians no longer need to limit religion to a purely subjective lyricism or to a ritual in itself, since it has become clear that the forms of the spirit – religion, art, philosophy – do not successively follow one another, but they work and live together; c)all those taking part in the process of argumentation in science, in theology, in philosophy, in the public life, need to be aware of the fact that their frontiers do not actually have the rigid character to which the people have been accustomed just by reading dictionaries or mere introductions. We do no favours either to science, philosophy or theology if we ignore the specifics of every one of them, but we are not realistic if we do not become aware of the fact that arguments for every one of them are dependent on each other.